Pendampingan Branding UMKM Makanan Ringan Melalui Pengelolaan Media Sosial - Bocca Della Verita; Poppy Febriana; Ainur Rochmaniah (Universitas Serang Raya, 2024)
The existence of technological developments can help all aspects of human life, includ-ing for business person. One place that can be utilized is social media. Social Media has a great opportunity to help MSMEs as a marketing tool for their products to a wider scope and create business competition in today's digital era. However, there are also many business person who still cannot balance their business with the arrival of the digi-talization era, as happened with